THE USE OF AUTHENTIC ASSESSMENT IN IMPROVING STUDENTS’ READING COMPREHENSION - Supardi, Firda Qotrunnada; Muljanto, Tanto Setia; Hasyim, Wahid (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This research was conducted to reveal the use of authentic assessment in improving students’ reading comprehension. The research method used in this study was quantitative method with the quasi-experimental design and it was conducted at one of Islamic Senior High School in Garut. The data were collected through the result of students’ pre-test and post-test. The result of this research showed that the post-test score was higher than the pre-test score. The result of data analysis showed that the tʹ observed in pre-test was -0.136 with the –t = 2.0570. Because the criterion was Ho accepted if -t ≤ tʹ, so it meant tʹ observed was in area of Ho accepted or Ha rejected. So, there was no significant difference in reading comprehension between two groups in the pre-test. While, after giving treatment to the experimental group, the result of post test showed that the tʹ observed was 5.32 with the –t = 2.056, it meant the result showed opposite from the pre-test because tʹ observed was in area of Ha accepted or Ho rejected So, there was significant difference in reading comprehension improvement on students who are treated by authentic assessment. This result hopefully would motivate the teachers to use authentic assessment in improving students’ reading comprehension.